Community empowerment in preventing anemia for women in Kalasey 2 Village, Minahasa Regency - Rudolf Boyke Purba; Joice Mermy Laoh; Olga Lieke Paruntu; Irza Nanda Ranti (Community Empowerment, 2023)
One of the nutritional problems that is commonly experienced in adolescence is anemia, which often occurs due to wrong nutritional behavior. Kalasey 2 Village is an area that has nutritional anemia problems in Mandolang District, Minahasa Regency. This community service aims to increase knowledge about anemia, prevent and overcome the problem of anemia in teenage girl and women of childbearing age (WUS). The methods used in this activity were checking hemoglobin levels, counseling on anemia and training on making red spinach juice. The results of this activity were young women and WUS as enthusiastic participants to prevent and overcome the problem of anemia in the village of Kalasey 2. Their knowledge of anemia increased after counseling. The results of the examination of hemoglobin levels, which is an indicator of anemia, also decreased from 41.1% to 29.4%. Furthermore, partners can overcome anemia by consuming red spinach juice and supported by the formation of the Anti Anemia Healthy Women (Waseanemia) group.